1992
DOI: 10.1063/1.858320
|View full text |Cite
|
Sign up to set email alerts
|

Contact angles

Abstract: Young [Philos. Trans. (1805)] derived an equation for the contact angle between a liquid–gas interface and a solid boundary, but doubts have been raised about its validity. This issue is reexamined on the basis of a new integral equation for the interface [J. B. Keller and G. J. Merchant, J. Stat. Phys. 63, 1039 (1991)]. The equation is solved asymptotically by the method of matched asymptotic expansions for small values of the range of intermolecular forces divided by a typical macroscopic length. The leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 11 publications
3
70
0
Order By: Relevance
“…Surprisingly, these arrived at contradicting conclusions. Merchant and Keller [5] derived a nonlocal integral equation for the interface profile that has essentially the same structure as in [8]. From asymptotic analysis they showed that the profile macroscopically approaches Young's angle, while the inner structure of the contact line displayed nontrivial oscillations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, these arrived at contradicting conclusions. Merchant and Keller [5] derived a nonlocal integral equation for the interface profile that has essentially the same structure as in [8]. From asymptotic analysis they showed that the profile macroscopically approaches Young's angle, while the inner structure of the contact line displayed nontrivial oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Inspection of the integrals reveals that these are simply the potential energy per unit volume at the free surface, due to the presence of liquid and solid molecules. The equilibrium condition is thus that h(x) is an equipotential [5,30]. Mechanically, a gradient in potential energy would lead to fluid motion.…”
Section: Microscopic Free Energy and Capillary Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…Immiscible two-phase flow in the vicinity of the contact line (CL), where the fluid-fluid interface intersects the solid wall, is a classical problem that falls beyond the framework of conventional hydrodynamics [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. In particular, molecular dynamics (MD) studies have shown relative slipping between the fluids and the wall, in violation of the no-slip boundary conditions [6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The boundary conditions are expressed at the same time on different surfaces by dynamic Laplace formulae, but also on the contact-line by a differential equation using the new term of line viscosity. This differential equation, namely the expression of the Young-Dupré condition of the dynamic contact angle, takes into account the line viscosity but also the inhomogeneousness of all types on the solid surface [9][10][11][12]. It gives the microscopic behaviour of the Young contact angle.…”
Section: Introductionmentioning
confidence: 99%